2016
DOI: 10.1093/cvr/cvw003
|View full text |Cite
|
Sign up to set email alerts
|

TBX5mutations contribute to early-onset atrial fibrillation in Chinese and Caucasians

Abstract: Our results provide both genetic and functional evidence to support the contribution of TBX5 gene in the pathogenesis of AF. The potential mechanism of arrhythmia may be due in part to the disturbed expression of ANP and CX40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…In addition, it is highly expressed in pleuroperitoneal folds, suggesting a role for this gene in diaphragm development, perhaps through interaction with GATA4 and GATA6 that are well‐established CDH genes. In support of its pathogenicity, the identified TBX5:p.(Ser372Leu) variant has been proven to cause a gain of function with an increase of Nppa promoter activation and a drastic reduction of TBX5‐NKX2.5 but not TBX5‐GATA4 physical interaction . Another case of syndromic CDH with aortic coarctation and nonspecified limb defects has been reported in association with variant TBX5:p (Asp111Tyr) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, it is highly expressed in pleuroperitoneal folds, suggesting a role for this gene in diaphragm development, perhaps through interaction with GATA4 and GATA6 that are well‐established CDH genes. In support of its pathogenicity, the identified TBX5:p.(Ser372Leu) variant has been proven to cause a gain of function with an increase of Nppa promoter activation and a drastic reduction of TBX5‐NKX2.5 but not TBX5‐GATA4 physical interaction . Another case of syndromic CDH with aortic coarctation and nonspecified limb defects has been reported in association with variant TBX5:p (Asp111Tyr) .…”
Section: Discussionmentioning
confidence: 96%
“…(Ser372Leu) variant has been proven to cause a gain of function with an increase of Nppa promoter activation 17,29 and a drastic reduction of TBX5-NKX2.5 but not TBX5-GATA4 physical interaction. 17 Another case of syndromic CDH with aortic coarctation and nonspecified limb defects has been reported in association with variant TBX5:p (Asp111Tyr).…”
Section: Discussionmentioning
confidence: 99%
“…In aggregate, this is a large increase in the number of loci for which we have a plausible gene target in the relevant tissue type when compared to eQTL studies alone. The results for peakHiCcalled genes were particularly encouraging in the combined analysis of cardiac electrophysiology traits where, in addition to known genes implicated in cardiac electrophysiology such as GJA5 (Christophersen et al, 2013;Gollob et al, 2006) and TBX5 (Ma et al, 2016;Nadadur et al, 2016), a global examination of biological processes associated with the genes identified yielded GO terms centered on the signal conduction and contraction of the myocardium.…”
Section: Connecting Cvd Risk Variants To Genes In the Heart 3d Genomementioning
confidence: 87%
“…Expression of NPPA was up-regulated in Pitx2 heterozygote and null mice [83]. Further, a recent study in a Chinese population suggested that TBX5 mutations increases the expression of ANP and connexin 40[107]. Senile accumulation of the protein aggregates may contribute to the predisposition to AF with aging.…”
Section: Transcriptomic Analyses and The Age Paradox In Afmentioning
confidence: 99%